Perbandingan Asuransi Syariah dan Asuransi Konvensional: Analisis dari Perspektif Ekonomi Islam - Marissa, Sasa; Rahma, Tri Inda Fadhila (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This research aims to compare sharia and conventional insurance from an Islamic economic perspective. The method used is a literature study of various related scientific sources. The results show significant differences between the two, particularly in the aspect of risk transfer. Conventional insurance involves elements of usury, gharar, and maisir, while Islamic insurance applies the principle of risk sharing as well as the concepts of ta'awun (mutual help) and mudharabah (profit sharing). The main challenge in implementing Islamic insurance is the low level of financial literacy and access to Islamic products, but it has great potential in increasing financial inclusion in Muslim-majority countries. In conclusion, Islamic insurance is more in line with Islamic economic principles and can be a fair and sustainable alternative in the insurance industry.